Heteroatom facilitated preparation of electrodes for sodium ion batteries - Bhosale, Manik E.; Banerjee, Abhik; Krishnamoorthy, Kothandam (RSC Advances, 2017)
A conjugated polymer comprising heterocycles was prepared and carbonized to obtain carbon with interlayer spacings between 0.42 and 0.37 nm and exhibited a specific capacity of 250 mA h g(-1).

Heteroatom-synergistic effect on anchoring polysulfides in chalcone-linked nanographene covalent organic frameworks for high-performance Li―S batteries - Ranjeesh, Kayaramkodath Chandran; Javaregowda, Bharathkumar H.; Gaber, Safa; Bhauriyal, Preeti; Kumar, Sushil; Skorjanc, Tina; Finsgar, Matjaz; Heine, Thomas; Krishnamoorthy, Kothandam; Shetty, Dinesh (Advanced Science, 2025)
Lithium-sulfur (Li & horbar;S) batteries are an attractive option for future energy storage devices because they offer higher theoretical specific capacity, energy density, and cost-effectiveness than commercial lithium-ion batteries. However, the practical applications of Li & horbar;S batteries are significantly limited by the shuttle effect caused by intermediate lithium polysulfides (LiPSs) and slow redox kinetics. In this study, the molecular engineering of chalcone-linked, sp(2)-bonded nanographene-type covalent organic frameworks (COFs) as sulfur hosts is reported to enhance interactions with LiPSs, thereby effectively suppressing the shuttle effect. The developed sulfur-hosting cathode material demonstrated outstanding battery performance, surpassing most reported materials by achieving a specific capacity of 1228 mA h g(-1) at 0.5C, with 80% retention after 500 cycles and an average Coulombic Efficiency (C.E.) of 99%. Additionally, the mechanisms of sulfur immobilization, the subsequent conversion into lithium polysulfides (LiPSs), and their binding energies with COFs are investigated using density functional theory (DFT) calculations. These findings offer valuable insights into the structure-property relationships essential for developing more efficient sulfur-hosting cathodes.
Keywords: anion-pi interaction; covalent organic frameworks; lithium-sulfur battery; nanographene; polysulfide shuttle